2013
DOI: 10.1245/s10434-013-3267-0
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Postoperative Complications and Clinical Cancer Outcomes

Abstract: This study investigated the relationship of surgical infectious complications in cancer patients with long-term survival for patients who had a number of different types of cancer. After taking into account the site, histology, and stage of the cancer, we found that patients with infectious complications had earlier death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Artinyan et al similarly demonstrated that the negative effect of perioperative morbidity on long-term outcomes after CRC resection was largely mediated by infectious complications [19]. In a separate study, Scaife et al queried the NSQIP database for solid malignancies and investigated the relationship of infectious complications with long-term outcomes [22]. The authors noted that infectious complications were associated with over a threefold increased risk of death in the long-term.…”
Section: Discussionmentioning
confidence: 99%
“…Artinyan et al similarly demonstrated that the negative effect of perioperative morbidity on long-term outcomes after CRC resection was largely mediated by infectious complications [19]. In a separate study, Scaife et al queried the NSQIP database for solid malignancies and investigated the relationship of infectious complications with long-term outcomes [22]. The authors noted that infectious complications were associated with over a threefold increased risk of death in the long-term.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative complications may result in shorter survival and impaired QoL, and the outcome of surgery depends profoundly on the frequency, severity grade and management of complications. 3 Comprehensive efforts have been made to define and classify severity grade of complications after pancreatic surgery, and the consensus definitions have been widely implemented. 4 However, a need to refine the concepts and redefine specific complications has recently been recognized.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that LC was negatively associated with these delayed recovery issues, including pelvic fluid collections and infections. This adds to the body of literature linking postoperative complications with worse oncologic outcomes in major gastrointestinal surgery .…”
Section: Discussionmentioning
confidence: 90%